The Impact of Using Cashless Payment during the Covid-19 Pandemic: A Case Study of Maybank - Daisy Mui Hung Kee; Nur Nuha Binti Nor Hisam; Nur Hidayu Binti Abd Rashid; Nur Sobbah Binti Abdul Aziz; Nur Aqilah Binti Mazlan; Nur Aimi Zayani Binti Mahadi (AIBPM Publisher, 2021)
The purpose of this study is to investigate the impact of using cashless payment during the Covid-19 pandemic. Maybank is the largest bank in Malaysia and listed as the top ranking of banking institutions. Maybank offers various types of services including cashless payment or e-payment methods. During the Covid 19 pandemic, most Malaysians would normally use their online payment since the physical distancing policy was encouraged by the World Health Organization (WHO). The study used articles, blogs, Wikipedia, and other information obtained from the website to collect data. The result shows that there are many positive impacts of using the cashless method.